Dissecting Pseudoaneurysm of the Proper Hepatic Artery Repaired by Primary Anastomosis: A Case Report - Roshan Razik; Aria Fallah; Charbel Sandroussi; Alice C. Wei; Ian D. McGilvray (Case Reports in Surgery)
Background. Although rare, visceral artery pseudoaneurysms often present as surgical emergencies with a specific mortality rate as high as 35% related to aneurysmal rupture. Risk factors for the development of iatrogenic pseudoaneurysms include anticoagulation, female gender, obesity, and vessel calcification. Case Report. We present a case of an elderly female who developed a dissecting pseudoaneurysm of the proper hepatic artery after undergoing routine surgery to resect a large duodenal adenoma. Surgical repair comprised of resection and primary anastomosis was employed resulting in a favourable outcome. Discussion/Conclusion. Surgical management reduces the risk of hepatic ischemia, biliary complications, and abscess formation. Although stenting, coil embolization, and thrombin injection are all plausible options for management, we propose that surgical reconstruction be considered seriously as a treatment for such spontaneous pseudoaneurysms.